1978
DOI: 10.1042/bj1730705f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on intrinsic factor and cobalophilin in different parts of the gastrointestinal tract of the pig

Abstract: The vitamin B(12) binders in the pig pyloric mucosa gastric and intestinal juice from the upper gastrointestinal tract were fractionated into only two molecular forms, classified as intrinsic factor and cobalophilin. The unsaturated vitamin B(12)-binding power due to cobalophilin was lower in the intestinal than in the gastric juice. Electrofocusing revealed that intrinsic factor and cobalophilin in the intestinal juice contained more of the ;neutral'-type isoproteins, and the suggestion is made that this is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Such an alkaline type of isoprotein does not represent a component of the native R protein (9,35). It most probably corresponds to denatured or partially hydrolyzed protein (9,14,16).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such an alkaline type of isoprotein does not represent a component of the native R protein (9,35). It most probably corresponds to denatured or partially hydrolyzed protein (9,14,16).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other concurrent (14) and more recent in vivo studies (17) demonstrated that IF free of Cbl remains biologically, immunologically, and physicochemically unaltered, whereas the R protein(s) are being degraded during normal intraluminal transport. These latter observations supported the thesis (16) that in EPI the R protein(s) are not subject to degradation and therefore the entire fraction of Cbl bound to these nonfunctional proteins will not be absorbed (14,16,17). Recent studies in Rothenberg's laboratory (18) indicated that bile effectively sequesters Cbl from IF to nonfunctional binders and that this process can be reversed after treatment with proteases (18).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sera were prepared from blood collected from pernicious anemia patients having circulating anti-IF antibodies. Rabbit anti-human R-binder (anti-R-binder) sera were produced using granulocyte preparations as antigen (10). Specific IF-receptor was solubilized from fresh porcine ileal mucosal scrapings as described (10).…”
mentioning
confidence: 99%